Nutritional fish pathology : - Tacon, A. G. J. (FAO, 1985)
In contrast to extensive and semi-intensive culture systems where fish obtain all or oart of their nutrient needs naturally available food organisms, fish maintained under intensive culture systems rely totally on the provision of a nutritionally complete diet throughout their culture cycle.